Spatial variation of physiologically equivalent temperature in different Local Climate Zones of a large city during a hot spell - Ines Langer; Elham Fakharizadehshirazi; Jochen Werner (Meteorologische Zeitschrift, 2021)
Global warming increases the risk of heat stress in Europe. Hence, heat stress must be considered as a health hazard for individuals working in outdoors and indoors conditions. Physiologically equivalent temperature (PET) is more related to the perceived temperature, but most of the current Local Climate Zone (LCZ) studies focus on measured temperature, instead of PET. Therefore, in this research, PET was applied to evaluate the thermal component of the outdoor microclimate for the first time in Berlin during a (1) hot spell, and (2) a normal period during July to August 2018. The aim of the present study is to explore the impacts of outdoor surroundings on human thermal comfort and its perception during the day and nighttime. Based on 32 micrometeorological stations located in different LCZs, the outdoor thermal sensation was investigated in order to find hourly thermal stress level conditions. Based on the mean hourly thermal sensation, the highest PET value was observed in, LCZ 4, “open high-rise” with 33.76 °C at 1400 CET, which represents a thermal stress level of “moderate heat stress”. The LCZ 2 showed “slight heat stress”, at the same time. High Sky View Factor (SVF) and relative humidity in “open high-rise” caused the highest PET. From the afternoon around 1800 CET to early morning 0600 CET, LCZ 2 is one thermal stress level warmer than all other existing LCZs in Berlin. During the hot spell, the hottest time period of the day was between 1600 CET to 1700 CET. In the morning from 0700 CET and midnight, the LCZ 2 was warmer than other local climate zones as the heat capacity of the buildings is high. Maximum hourly PET values illustrate that LCZ 4 was the warmest LCZ in which thermal sensation was ‘very hot’ between 0800 CET to 1700 CET. According to minimum hourly of PET, LCZ 4 was the coldest LCZs during the night and early in the morning.